Drug Repurposing for Paracoccidioidomycosis Through a Computational Chemogenomics Framework - de Oliveira, Amanda Alves; Neves, Bruno Junior; Silva, Lívia do Carmo; Soares, Célia Maria de Almeida; Andrade, Carolina Horta; Pereira, Maristela (Frontiers in Microbiology, 2019)
Paracoccidioidomycosis (PCM) is the most prevalent endemic mycosis in Latin America. The disease is caused by Paracoccidioides and mainly affects low-income rural workers after inhalation of fungal conidia suspended in the air. The current arsenal of chemotherapeutic agents requires long-term administration protocols generally extended by two or more years. In addition, chemotherapy is related to a significantly increased frequency of disease relapse, high toxicity, and incomplete elimination of the fungus. Due to the limitations of current anti-PCM drugs, we developed a computational drug repurposing-chemogenomics approach to identify approved drugs or drug candidates in clinical trials with anti-PCM activity. Contrary to the one-drug-one-target paradigm, our chemogenomics approach attempts to predict potential interactions between all drugs and all Paracoccidioides protein targets. To achieve this goal, we designed a workflow with the following steps: (a) compilation and preparation of Paracoccidioides spp. genome data; (b) identification of orthologous proteins among three genome isolates; (c) identification of homologous proteins in publicly available drug-target databases; (d) selection of Paracoccidioides essential targets using known validated genes from Saccharomyces cerevisiae; (e) realization of homology modeling and molecular docking studies; and (f) experimental validation of selected candidates. We prioritized 14 compounds; among them, two antineoplastic drug candidates (vistusertib and BGT-226) predicted to be inhibitors of phosphatidylinositol 3-kinase TOR2 showed antifungal activity at low micromolar concentrations (<10 µM). In parallel, four antifungal azole drugs (bifonazole, luliconazole, butoconazole, and sertaconazole) not yet used in PCM chemotherapy showed antifungal activity at low nanomolar concentrations, validating our methodology. Consequently, we are confident that our strategy for predicting new anti-PCM drugs is useful. Finally, we could recommend prospective hit-to-lead optimization studies to improve potency and selectivity, as well as pharmaceutical formulations to improve oral bioavailability of identified antifungal azoles.